Study on the relationship between Vitamin D deficiency and Leukocyte Ratio in Multidrug Resistant Tuberculosis patients - Fardiah Tilawati Sitanggang; James Perdinan Simanjuntak; Siti Sakdiah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Tuberculosis (TB) remains an important health problem in Indonesia,the problems more complex with phenomenon of multi-drug resistance Tuberculosis (MDR) which cause worse prognosis, long treatment,high risk of transmission to other and side effect of treatment. Vitamin D plays a role in non specific and specific immune responses in Mycobacterium tuberculosis (M.tb) infection. Vitamin D have a role in hematopoiesis and affects the early development of monocytes and granulocytes. M.tb infection causes changer in the ratio of neutrophil cells, lymphocytes and monocytes. Changes in the ratio reflect an increase or decrease of effective immune response. Using a case control design, this study will evaluate the correlation between vitamin D, leukocyte ratio and MDR-TB patients among MDR-TB patient cases and TB patient controls. Independent variable in this study were vitamin D levels, leukocyte ratios consisting of NLR, MLR, NMLR, and clinical status of respondents were the dependent variable. The result of this study found that vitamin D levels of TB patients all showed values ​​that were within range of in the insufficiency and deficiency categories. From this result TB patients must coverIn addition, the NLR and NMLR parameters were able to show that immune status problems were mainly found in the MDR-TB patients